Master’s Degree Students’ Experience Towards Feedback on the Thesis Writing - Panday, Nikesh (Kalika Journal of Multidisciplinary Studies, 2025)
This study, entitled Master’s Degree Students’ Experience Towards Feedback on the Thesis Writing investigates master’s degree students’ experiences with feedback and expectations during thesis composition at Tribhuvan University. This qualitative research examines how students perceive, interpret, and respond to supervisor feedback, recognizing that good thesis supervision involves intricate emotional, relational, and intellectual aspects. Data were collected via semi-structured interviews with recent graduates who evaluated their supervisory interactions and feedback mechanisms. Thematic analysis revealed three primary themes: roles of supervisors’ feedback in thesis writing, explicit and directed feedback, and expectations from the supervisor. The findings underscore the essential function of supervisors in delivering clear, prompt, and constructive feedback, which profoundly influences students’ motivation, emotional reactions, and academic autonomy. The research concludes that misaligned or unarticulated expectations between students and supervisors can result in frustration and hinder advancement, highlighting the importance of clear agreements and continuous communication. Recommendations include establishing organized institutional frameworks for feedback dissemination, providing professional training for supervisors on effective feedback methodologies and emotional intelligence, and enhancing student feedback literacy. Ganeshman Singh Multiple Campus